Apnavan Plantations in Arunachal Pradesh: an Agro-forestry Scheme for Rehabilitation of Degraded Jhum Lands through People’s Participation - Gupta, Vishal (Indian Forester, 2004)
Owing to geographical isolation and topographical remoteness, the diverse tribal groups of Arunachal Pradesh have traditionally been practicing Jhum cultivation for ages. Jhum has reportedly affected some 0.23 million ha land ofthe State and nearly 54,000 families are reported to be subsisting on this age old practice. A scheme under the name Apnavan was initiated by the Department of Environment & Forests of the State to rehabilitate the degraded Jhum areas by involving the local people using agro-forestry practices. The scheme has been there for over a decade and an area of 13,645 ha has been developed from 1990-1991 to 2000-2001. This paper attempts to analyze the various issues related to the scheme, the progress achieved so far and the major constraints in the way of its successful implementation.